2019
DOI: 10.3390/ijms20194826
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Nuclear Exporter Protein XPO1/CRM1 in Gastric Cancer

Abstract: Gastric cancer remains an unmet clinical problem in urgent need of newer and effective treatments. Here we show that the nuclear export protein, Exportin 1 (XPO1, chromosome region maintenance 1 or CRM1), is a promising molecular target in gastric cancer. We demonstrate significant overexpression of XPO1 in a cohort of histologically diverse gastric cancer patients with primary and metastatic disease. XPO1 RNA interference suppressed gastric cancer cell growth. Anti-tumor activity was observed with specific in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 49 publications
(78 reference statements)
2
31
0
Order By: Relevance
“…Interestingly, in a distinct study, selinexor was shown to overcome TKI resistance in a leukemia model [18]. Moreover, a recent study from our lab has demonstrated that XPO1 may act as a promising molecular target in gastric cancer and blocking it using SINE compounds can have therapeutic significance [19]. In alignment to these studies, our RNA seq analysis showed activation of cargo receptor activity and nuclear pore signaling molecules in the resistant thyroid cell line.…”
Section: Discussionsupporting
confidence: 67%
“…Interestingly, in a distinct study, selinexor was shown to overcome TKI resistance in a leukemia model [18]. Moreover, a recent study from our lab has demonstrated that XPO1 may act as a promising molecular target in gastric cancer and blocking it using SINE compounds can have therapeutic significance [19]. In alignment to these studies, our RNA seq analysis showed activation of cargo receptor activity and nuclear pore signaling molecules in the resistant thyroid cell line.…”
Section: Discussionsupporting
confidence: 67%
“…In fact, both fusion proteins can bind CRM1 and its co-factor, the small GTPase Ran, and inhibit the nuclear export of NES-containing proteins and RNPs [22,23,25]. Targeted CRM1 inhibition by small molecule antagonists has become an appealing anti-cancer strategy, for both solid and hematologic malignancies [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Leptomycin B (LMB), a fungal metabolite from Streptomyces spp, was the first identified small molecule inhibitor specifically targeting CRM1 [41].…”
Section: Introductionmentioning
confidence: 99%
“… 54 XPO1 overexpression was found to be a therapeutic target in GC and we have found blocking the protein with the small FDA approved molecule selinexor (XPOVIO) influences the expression of a subset of tumor-associated miRNAs. 55 Furthermore, we have found via small RNA sequencing that after XPO1 inhibition with selinexor as well as the second generation inhibitor KPT-8602, miR-7977 ( CWH43 interacting miRNA) is significantly upregulated (fold change 2.22, P = 3.92E-23 and fold change 2.08, P = 5.46E-20) in the early stage diffuse gastric cell line SNU-1 suggestive of the tumor suppressive role of this miRNA. The connection between nuclear export and cancer-specific miRNAs in GC has not been investigated in depth.…”
Section: Resultsmentioning
confidence: 96%
“…54 XPO1 overexpression was found to be a therapeutic target in GC and we have found blocking the protein with the small FDA approved molecule selinexor (XPO-VIO) influences the expression of a subset of tumor-associated miRNAs. 55 Furthermore, we have found via small RNA sequencing that after XPO1 inhibition with selinexor as well not been investigated in depth. We are working toward not only characterizing this novel interaction but also using this information to uncover novel genes pertinent to GC growth and development.…”
Section: Genetic Analysis Of Downregulated Gc Genesmentioning
confidence: 99%